Religious propaganda and missionary competition in the New Testament world : essays honoring Dieter Georgi - Georgi, Dieter.; Bormann, Lukas.; Del Tredici, Kelly.; Standhartinger, Angela. (Novum Testamentum, Supplements, 1994)
Religious Propaganda is a pivotal concept for the Hellenistic and Roman epochs in the History of Religions. The term refers to the various competing religious and philosophical movements and currents during those periods. Renowned scholars (H. Attridge, K. Baltzer, J. Collins, A. Dewey, H. Koester, A.T. Kraabel, D. Lührmann, J. Robinson, W. Schottroff, E. Schüssler Fiorenza, A. Yarbro Collins and others) interpret Pagan, Jewish, and Christian sources with a view toward elucidating the confrontation of Jewish and Christian groups with their respective social, economic, religious, and political contexts. The authors seek to demonstrate the significance of missionary and propagandistic themes as well as strategies for the self-understanding of Jews and Christians at the turn of the eras. The articles, 25 in all, draw upon the broad expanse of scholarly work in the History of Religions pertaining to this period: the authors discuss methodology and the state of research, and they forge ahead in the exploration of the intertestamental and New Testament writings.